The Ex Ante Effects of Bankruptcy Reform on Investment Incentives - Robert K. Rasmussen (Washington University Law Quarterly, 1994)
To assess the ex ante costs of bankruptcy reform, Part I of this Article begins with an examination of the literature on the agency costs in corporations. The costs arise both with the division of ownership among different claimholders and with the separation of ownership and control. Implicit in this literature is the assumption that bankruptcy law respects the contractual priority among the various claimants of the firm. It is well known, however, that bankruptcy law in practice deviates from contractual priority. Shareholders generally receive payouts even though the firm is insolvent. Part II examines the way in which this deviation affects the decisions of those charged with running the firm prior to the filing for bankruptcy. Part III compares these effects with the effects associated with the various proposed replacements for current law. Part IV sets forth the implications of these results for bankruptcy reform.
Keywords: Bankruptcy law; Corporation law; United States; Investments; Corporate governance; Bankruptcy